2018
DOI: 10.1136/bmjoq-2017-000238
|View full text |Cite
|
Sign up to set email alerts
|

Are they high on steroids? Tailored interventions help improve screening for steroid-induced hyperglycaemia in hospitalised patients

Abstract: Steroid-induced hyperglycaemia (SIH) is a common adverse effect in patients both with and without diabetes. This project aimed to improve the screening and diagnosis of SIH by improving the knowledge of healthcare professionals who contribute to the management of SIH in hospitalised patients. Monitoring and diagnosis of SIH were measured in areas of high steroid use in our hospital from May 2016 to January 2017. Several interventions were implemented to improve knowledge and screening for SIH including a staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…One of the common ways to do this is to drastically reduce the lecture length to allow opportunity for reflection or activity following. 24 Previous work we have conducted has demonstrated that a short lecture in the postgraduate setting provided a beneficial change in knowledge for junior doctors 25 26 demonstrating their use when applied correctly.…”
Section: Introductionmentioning
confidence: 98%
“…One of the common ways to do this is to drastically reduce the lecture length to allow opportunity for reflection or activity following. 24 Previous work we have conducted has demonstrated that a short lecture in the postgraduate setting provided a beneficial change in knowledge for junior doctors 25 26 demonstrating their use when applied correctly.…”
Section: Introductionmentioning
confidence: 98%